Implementasi Nilai – Nilai Religius Bagi Peserta Didik (Studi Pada MI Terpadu Darul Ulum dan SD Negeri 5 Lempuyang Bandar) - Wulandari, Iis; Subandi, Subandi; Jannah, Raudlatul; Mispani, Mispani (Attractive : Innovative Education Journal, 2020)
The aim of this study was to analyse religious values who ​​developed for students and their implementation their religious values at elementary school 5 and Madrasah Ibtidahya Terpadu Darul Ulum Lempuyang Bandar Way Pangubuan sub district. The researchers used qualitative research by using comparative studies. The result showed that in implementing religious values ​​are through school culture such as accustoming greetings in the school environment, providing exemplary, spontaneous greetings in the school environment. Keywords: Religious Values, Education Character, Implementation Religious Values